Pengembangan Media Pembelajaran Berbasis Game Roda Putar pada Materi Rukun Sholat Kelas 3 di SDIT Baiturrahim - Junaidi Junaidi; Supratman Zakir; Iswantir M; Deswalantri Deswalantri (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2023)
This research was conducted based on the existence of problems that have been observed by the author's lack of student motivation in learning the pillars of prayer by using the spin wheel game media so that students are less active in the learning process. to attract students' learning interest. The purpose of this study was to produce a valid, practical and effective design of supporting media for learning Islamic religious education based on spin-wheel games. The method used in this study is the research and development (R&D) method using the 4D model according to Thiagarajan (1974), there are 4 stages, namely the abbreviation of Define, Design, Develop and Disseminate. There are three product tests conducted in this study, namely validity tests, practicality tests and effectiveness tests conducted by experts. Based on the results of product tests that have been carried out by the author from the validity test, the average value is 0.87 which is declared valid, and for the practicality test, the average value is 1.00 which is declared practical and for the effectiveness test, the average value is obtained. -the average is 0.59 which is declared effective.